Resiliensi Teologis-Etis Terhadap Model Ibadah Kristiani di Tengah Pandemi Covid-19 - Daniel Fajar Panuntun; Yohanes Krismantyo Susanta (Institut Agama Kristen Negeri Manado, 2021)
Corona Virus Disease 2019 (Covid-19) is a pandemic with a global impact. This virus has spread since December 2019 from China. Covid-19 is very fast spreading and is deadly, so this has caused global fears, including Indonesia. The Government of Indonesia is pursuing measures to minimize the spread of Covid-19 through social restrictions that impact the Christian worship model. This paper aims to determine the theological-ethical resilience of Christian worship model during the co-19 pandemic. The study was conducted with a qualitative approach to the types of social and theological research through literature studies. This study produces an explanation of the ethical theological resilience of the worship model, which consists of 4 items description of the worship model explanation.